Peranan IPK dan Soft Skill dalam Proses Rekrutmen dan Seleksi Fresh Graduate : Tanggapan dan Harapan Perusahaan Peserta Job Fair di UKSW - Fariani Nunik (Jibaku: Jurnal Ilmiah Bisnis, Manajemen dan Akuntansi, 2021)
In the recruitment and selection process in general, one of the indicators that is often used for college graduates is the Grade Point Average (GPA). Besides that, soft skills are also needed. The purpose of this research is to find out the opinion of the companies participating in the Job Fair on the role of GPA and soft skills in the recruitment and selection process for fresh graduates, what methods are used by job fair participating companies to assess the soft skills of fresh graduates and to find out what are the expectations of the participating companies. job fair on the ability of soft skills for fresh graduates in the future. The population of this study is all companies participating in recruiting applicants through the company job fairs that are participating in the SWCU Job Fair on March 6 and 7, 2014. The sampling technique uses saturation sampling. The sample in this study were companies that specifically opened vacancies from economics graduates. The results showed that the opinion of companies that participated in job fairs in assessing GPA was to standardize a high GPA because it was the main requirement but not absolute, because it was still supported by soft skill assessments. The method used by the company to assess soft skills is by using the interview method. The hopes for fresh graduates to have more soft skills, such as having more motivation and morale, having high self-confidence, practicing more communication skills and being more honest and working hard.Keywords:Recruitment, selection, ipk, softskill